Chemical and pharmacological characterization of hypolipidemic compound from Cajanus Cajan - Md. Anwar Habib, Abu Syed Md Anisuzzaman, Md. Rofiqul Islam Khan, Md. Abdul Gafur (Bangladesh Pharmacological Society, 2010)
The study was carried out to identify the compound responsible for hypolipidemic and hypoglycemic effects of Cajanus cajan (redgram). The methanol extract of redgram seeds were fractionated into petroleum ether, chloroform, and methanol. The methanol fraction significantly decreased fasting blood glucose, and lipid profiles (p<0.001) on streptozotocin-induced mice compared to control. The methanol fraction was then subjected to chromatographic analysis and a compound (CCA1) has been isolated. The structure of the compound is considered to be substituted cyclopentene with glucose by analysis its 1H and 13C-NMR data. Biological studies of the isolated compound possessed prominent hypolipidemic activity. Although a number of hypoglycemic compounds are reported, yet not any hypolipidemic compound from redgram. The compound CCA1 seems to be the first report on hypolipidemic activity from methanol extract of redgram.